Christian mission and Diakonia in Lebanon: Theological foundations, historical witness, and contemporary praxis - Fahed, Ziad (Transformation, 2025)
This article examines the mission of the Christian churches in Lebanon through the lens of diakonia, understood as service that is theological, prophetic, and transformative. Drawing on Scripture, conciliar teaching, papal encyclicals, and Lebanese ecclesial voices, it argues that diakonia is constitutive of the Church’s identity. The historical experience of Lebanese churches during war, occupation, displacement, and economic collapse shows how service has been tested, reshaped, and extended across denominational and religious boundaries. Case studies of Caritas, World Vision, Offre Joie, Oum el Nour, and the Dialogue for Life and Reconciliation illustrate how ecclesial visions of service are translated into humanitarian relief, reconciliation, and peacebuilding. In Lebanon’s “long emergency,” diakonia becomes proclamation, solidarity becomes reconciliation, and opting for life itself a theological confession. The article concludes by asking how such witness can remain both prophetic and sustainable in the face of state collapse and sectarian fragmentation.